Marcas tateadas nas publicações científicas sobre educação geográfica de cegos - Zatta, Ediane Freider (2025)
Inclusive education seeks to guarantee opportunities for schooling for those who, for one reason or another, have signs of some biological or cognitive limitation, which require specific teaching procedures, to enable learning and coexistence with other students in regular schools. However, the inclusion of blind people, especially in the Geography curriculum component, is still a challenge to be overcome, as it is a complex issue, which involves significant limits both in pedagogical practice and in the training of educators. Since Geography is composed of visual cartographic representations, such as maps, graphs, globes and various types of images, some of these are often inaccessible to blind students. This limitation and the dependence on tactile resources can create barriers to the participation of these students in the educational process. This is one of the problems of including blind people in geography education, which manifests itself in the lack of teaching materials adapted to tactile maps as support, which makes it difficult to understand geographic content. Furthermore, inadequate teacher training in inclusive methodologies can result in pedagogical practices that do not meet the specific needs of blind students. Therefore, research on the inclusion of blind students lies in the need to promote a truly inclusive education that respects and values diversity. We sought to identify the barriers faced by blind students in the teaching of Geography, through what is presented in scientific productions on geographic education. Thus, this dissertation presents some of the possible marks that can be felt in scientific publications on geographic education for the blind, in the relationship between research and geographic education. The main objective was to analyze how the educational process in Geography, for blind students, has been approached in the last 11 years, through scientific productions . This research was developed in the Postgraduate course in Geography at the University of Western (Unioeste/FB), in the city of Francisco Beltrão Paraná, in the research line: Education and Teaching of Geography. We traced the methodological path through the state of the art, focusing on scientific productions that address issues related to blind students. The research corpus included 20 journals, 21 dissertations, and seven theses in the area of Geography. The intention was to determine which information leads to the path of knowledge, coming from communications in scientific journals, in theses, and dissertations, related to the education of blind people. The time frame includes the period from 2012 to 2023, since during this period there was a great evolution of public policies for inclusion. The analysis allowed us to highlight some aspects of how the policies impacted the education of blind students, the advances and challenges for such students, highlighting what is discussed and constructed in this context of the relevance of cartography for the blind and the importance of actions of the inclusive methodology, which can significantly improve the teaching and learning of Geography.